Association between weight loss and reduced use of antihypertensive, hypoglycemic, psychotropic, and lipid-lowering drugs in patients undergoing bariatric surgery - Mariana Mendes Pereira Gonçalves; Frederico Daldegan; Gabriel Correia Iannuzzi; Marcelo Mendonça Rodrigues; Seleno Glauber de Jesus-Silva (Hospital de Clínicas de Itajubá, 2021)
Objectives: To analyze whether the weight reduction observed in bariatric surgery (Roux-en-Y gastric bypass; BGYR) is accompanied by a reduction in the use of antihypertensive, hypoglycemic, antilipidemic, and psychotropic drugs after 6 and 12 months. Methods: Longitudinal, retrospective study of 100 adult patients undergoing RYGB from May 2015 to January 2019, by laparotomy or laparoscopy. Data on age, body mass index (BMI), and the number of drugs used were recorded 6 and 12 months after surgery. Results: The mean age was 39.7 ± 9.7 years, and the majority were female (n = 78). The mean preoperative BMI was 43.7 ± 5.1 kg/m2, and the mean reduction in BMI after 6 months was 12.1 kg/m2 and 14.9 kg/m2 after 12 months. The reduction in antihypertensive drugs was 65.2% after 6 months and 96% after 12 months. The reduction in 6 months of hypoglycemic agents was 84.3%, and in 12 months, 98.3%. The average reduction in antidyslipidemic drugs was 86.7% in 6 months, and there was no record of using this medication after 12 months. Psychotropics showed a temporary reduction in use after 6 months with a return to levels close to the baseline after 1 year.There was no correlation between the variation in BMI and the use of drugs. Conclusions: there was a significant reduction in the use of drugs after 6 and 12 m, except for psychotropic drugs. The reduction in the use of drugs was not correlated with a reduction in BMI.